1993
DOI: 10.1111/j.1365-2605.1993.tb01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Immuno‐competent cells in the murine epididymis following infection with Escherichiu coli

Abstract: Epididymitis was induced by retrograde injection of Escherichia coli into the vas deferens of 28 mice. A group of 28 saline-injected animals served as controls. On Days 1, 3, 7 and 28, groups of seven animals were killed. Bacterial culture was performed. Leucocyte numbers and distribution were determined in epididymides. In infected mice, E. coli were isolated from all epididymides on Days 1 and 3, but only from five of seven epididymides on Days 7 and 28. One week after infection, the total number of macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The immune system eradicated the pathogen in several epididymes 3 and 6 months after infection. That immune mechanisms may clear the epididymal aspirate and tissue from pathogens in a proportion of cases has been reported previously in the rabbit [9] and mouse [11] models of experimental E. coli epididymitis. Nashan et al [11] suggested that successful phagocytotic activity of macrophages was the predominant mechanism, by characterizing the sequence of cellular events using monoclonal antibodies.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The immune system eradicated the pathogen in several epididymes 3 and 6 months after infection. That immune mechanisms may clear the epididymal aspirate and tissue from pathogens in a proportion of cases has been reported previously in the rabbit [9] and mouse [11] models of experimental E. coli epididymitis. Nashan et al [11] suggested that successful phagocytotic activity of macrophages was the predominant mechanism, by characterizing the sequence of cellular events using monoclonal antibodies.…”
Section: Discussionsupporting
confidence: 67%
“…That immune mechanisms may clear the epididymal aspirate and tissue from pathogens in a proportion of cases has been reported previously in the rabbit [9] and mouse [11] models of experimental E. coli epididymitis. Nashan et al [11] suggested that successful phagocytotic activity of macrophages was the predominant mechanism, by characterizing the sequence of cellular events using monoclonal antibodies. However, in contrast to other reports [9,14], although E. coli was not detected in the present contralateral epididymis, with no antimicrobial treatment viable pathogens could be re-isolated up to 3 months after the initial infection in epididymal and up to 6 months later in prostate tissue.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations